120k views
4 votes
Simplify:

5/4 + 4 (3/4 - 1/2)^2

1 Answer

3 votes

= > (5)/(4) + 4 {( (3)/(4) - (1)/(2) )}^(2) \\ \\ \\ \\ = > (5)/(4) + 4( (3)/(4) - (1 * 2)/(2 * 2) ) {}^(2) \\ \\ \\ \\ = > (5)/(4) + 4( (3)/(4) - (2)/(4) ){}^(2) \\ \\ \\ \\ = > (5)/(4) + 4( (3 - 2)/(4) ) {}^(2) \\ \\ \\ \\ = > (5)/(4) + 4( (1)/(4) ) {}^(2) \\ \\ \\ \\ = > (5)/(4) + 4( (1 * 1)/(4 * 4) ) \\ \\ \\ \\ = > \: (5)/(4) +4 ((1)/(16) )\\ \\ \\ \\ = > ( (5)/(4) + (1)/(4) ) \\ \\ \\ \\ => (5+1)/(4) \\ \\ \\ \\ (3)/(2)
User Laurence Burke
by
5.3k points